HDR endobronchial brachytherapy in palliative and combined radical treatment of lung cancer - Fijuth, Jacek (J Contemp Brachytherapy, 2010)
In patients with advanced or metastatic lung cancer who present predominantly with dyspnoea and haemoptysis the use of HDR brachytherapy has been proven an effective method of palliation. The application of brachytherapy as a boost to EBRT in curative cases is much more restricted. It can be considered in a selected group of patients with dominating endobronchial disease, who are medically inoperable, or have small or occult carcinomas of the lung.